Modern Jewish literatures : intersections and boundaries - Lerner, L. Scott; Kramer, Michael P., 1952-; Jelen, Sheila E. (Jewish culture and contexts., 2011)
Is there such a thing as a distinctive Jewish literature? The authors of the fifteen essays in this volume find the answer in a shared endeavor to use literary production and writing in general as the laboratory in which to explore and represent Jewish experience in the modern world.